2013
DOI: 10.1021/es402838f
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Formation of Mono- and Dihydroxylated Polychlorinated Biphenyls by Rat Cytochrome P450 2B1

Abstract: Changes in atropisomer composition of chiral polychlorinated biphenyls (PCBs) and their mono- and di- hydroxylated metabolites (OH- and diOH-PCBs) via rat cytochrome P450 2B1 (CYP2B1) mediated biotransformation were investigated in vitro. Rat CYP2B1 could stereoselectively biotransform chiral PCBs to generate meta-OH-PCBs as the major metabolites after 60 min incubations. Non-racemic enantiomer fractions (EFs: concentration ratios of the (+)-atropisomer or the first-eluting atropisomer over the total concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
140
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 77 publications
(149 citation statements)
references
References 48 publications
9
140
0
Order By: Relevance
“…A convenient nomenclature for PCB metabolites has been proposed by Maervoet et al and, as shown for PCB 136 in Fig 3, will be used throughout this manuscript (Maervoet et al 2004). The oxidation of C-PCBs, in particular those with a 2,3,6-trichloro substitution pattern in one phenyl ring, to HO-PCBs has been studied extensively using recombinant enzymes (Lu et al 2013, Lu and Wong 2011, Waller et al 1999, Warner et al 2009), hepatic microsomes (Kania-Korwel et al 2011, Kania-Korwel and Lehmler 2013, Schnellmann et al 1983, Wu et al 2014, Wu et al 2011), isolated hepatocytes (Vickers et al 1986) and, liver, hippocampus and skin slices (Garner et al 2006, Wu et al 2013a, Wu et al 2013b) obtained from mammalian species. To the best of our knowledge, the oxidation of C-PCBs in non-mammalian species, such as amphibians, fish or avian species, has not been investigated to date.…”
Section: Metabolism Of C-pcbs To Ho-pcbsmentioning
confidence: 99%
See 2 more Smart Citations
“…A convenient nomenclature for PCB metabolites has been proposed by Maervoet et al and, as shown for PCB 136 in Fig 3, will be used throughout this manuscript (Maervoet et al 2004). The oxidation of C-PCBs, in particular those with a 2,3,6-trichloro substitution pattern in one phenyl ring, to HO-PCBs has been studied extensively using recombinant enzymes (Lu et al 2013, Lu and Wong 2011, Waller et al 1999, Warner et al 2009), hepatic microsomes (Kania-Korwel et al 2011, Kania-Korwel and Lehmler 2013, Schnellmann et al 1983, Wu et al 2014, Wu et al 2011), isolated hepatocytes (Vickers et al 1986) and, liver, hippocampus and skin slices (Garner et al 2006, Wu et al 2013a, Wu et al 2013b) obtained from mammalian species. To the best of our knowledge, the oxidation of C-PCBs in non-mammalian species, such as amphibians, fish or avian species, has not been investigated to date.…”
Section: Metabolism Of C-pcbs To Ho-pcbsmentioning
confidence: 99%
“…The low affinity reaction had an apparent K m of 645 μM and a V max of 367 pmoles/min/mg hepatocyte. Several recent studies using pure PCB 132 and 136 atropisomers suggest that the respective atropisomers interfere with each other’s metabolism by CYP2B1 (Lu et al 2013, Lu and Wong 2011), and further studies of the enzyme kinetics of pure PCB atropisomers are needed.…”
Section: Metabolism Of C-pcbs To Ho-pcbsmentioning
confidence: 99%
See 1 more Smart Citation
“…A major mechanism for changing EFs of PCBs is from stereoselective metabolism by CYPs [33]. For example, enantioselective biotransformation of chiral PCBs in the plant leaves may possibly be due to metabolism by CYP enzymes there [20].…”
Section: Enantioselectivity In Accumulationmentioning
confidence: 99%
“…The formation of neurotoxic metabolites like 4-OH-PCB 136 may play a role in the developmental neurotoxicity of PCBs [7]. PCBs 91, 95 and 136 can be stereoselectively biotransformed to OH-PCB and dihydroxylated metabolites (diOH-PCB) by rat CYP2B1 in vitro, with significantly higher biotransformation activities of (+)-PCB 91 (E1-PCB 91), (+)-PCB 95 (E2-PCB 95), and (+)-PCB 136 but no apparent stereoselectivity for PCB 149 [33]. The formation rate of 5-OH-PCBs formation is congener-specific for these four PCBs.…”
Section: Enantioselectivity In Accumulationmentioning
confidence: 99%